2020
DOI: 10.32473/edis-fe1065-2019
|View full text |Cite
|
Sign up to set email alerts
|

Economic Value of Florida Water Resources: Contributions of Tourism and Recreation to the Economy

Abstract: This paper is a part of the EDIS series “Economic Value of Florida Water Resources” and it presents results from economic studies examining benefits from water-based recreation in Florida. Our special focus is freshwater-based recreation. Specifically, studies examining the “economic contribution” or “economic impact” of recreation activities around various natural sites are discussed. Interested reader can pick and choose the studies most relevant to his/her area of interests or those discussing recreational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For example, spring-based tourism provides a significant contribution to the economy, with the valueadded for 15 major springs in the study area estimated at $52.58 million in 2014 (Borisova et al, 2018). Further, Wu et al (2018) showed that the estimated average springbased recreation trip was valued by the tourists at $28.91 per person per trip, which can be translated into the total recreational value for four major springs in the study area of about $25 million annually (Borisova et al, 2020;Wu et al, 2018). Continued spring degradation is expected to reduce the value assigned by the tourists to the spring-based recreation trips, the number of visitors, and the resulting tourism contribution to the regional economy.…”
Section: Discussionmentioning
confidence: 92%
“…For example, spring-based tourism provides a significant contribution to the economy, with the valueadded for 15 major springs in the study area estimated at $52.58 million in 2014 (Borisova et al, 2018). Further, Wu et al (2018) showed that the estimated average springbased recreation trip was valued by the tourists at $28.91 per person per trip, which can be translated into the total recreational value for four major springs in the study area of about $25 million annually (Borisova et al, 2020;Wu et al, 2018). Continued spring degradation is expected to reduce the value assigned by the tourists to the spring-based recreation trips, the number of visitors, and the resulting tourism contribution to the regional economy.…”
Section: Discussionmentioning
confidence: 92%
“…Recreation is one of the most listed freshwater ecosystem services documented in the literature (see Böck et al, 2018; Hanna et al, 2018; Kaval, 2019; Vári et al, 2021). Beyond human well‐being, recreational services often contribute to local and regional economies (e.g., Borisova et al, 2020; Getzner, 2015; Sánchez et al, 2021) and have the potential to engage large numbers of people in and around freshwater bodies. With over 4.55 billion social media users, the opportunity to connect with others through these platforms is powerful, though under‐used to promote freshwater biodiversity conservation (He et al, 2021).…”
Section: Non‐materialsmentioning
confidence: 99%